The Influence of the Principle of Negbinism on the Development of Students (On the Example of The Spiritual Heritage of Eastern Thinkers) - Yakubova Shakhnoza Erkinbaevna (Genius Journals, 2023)
In this article, a comparative analysis of the sources that create a special talent of a positive worldview among students, as well as creative ways of forming the concept of optimism in the student's thinking based on the scientific heritage of the scholars of the East is described
Keywords: Naqshbandi; personality; education